Efeitos do pastoreio sobre a vegetação natural em fragmento de Savana Estépica Parque, Rio Grande do Sul, Brasil - Redin, Cristina Gouvêa (2013)
Despite occupying a prominent place in the southern flora, the region belonging to the State Park Espinilho inserted within Steppe Savanna Park domains still is poorly investigated by science. Vegetation characteristics such as dense herbaceous extract and the presence of isolated trees configure it as favorable to livestock activity. Taking advantage of this fact, the aimed of the present study was to analyze the floristic and edaphic changes imposed by grazing. For this we select two areas, one under grazing and other excluded from this activity for five years, both areas contain a sample unit of 2ha subdivided into 200 plots of 100m² subunits. An inventory of the woody and regenerating extract was conducted in 100 of these sampling units and the data of other variables were collected in 50 subunits. The dissertation was divided in two chapters with the objective of analyzing the similarity, the structural and floristic changes in regenerating and woody vegetation (Chapter I) and evaluate changes in physical properties of the soil and total aerial herbaceous biomass between areas, as well as investigating possible correlations between these variables and the abundance of the main species present in regeneration (Prosopis affinis Spreng. and Vachellia caven (Molina) Seigler & Ebinger (Chapter II). Through studies on structural and phytosociological attributes we can see remarkable differences between areas mainly on the diameter structure of vegetation and floristic composition of natural regeneration and being Vachellia caven the specie better adapted to grazing than Prosopis affinis. As a result expressed by Jaccard index, the similarity between areas is average (75%). Regarding the physical variables of soil and total aboveground herbaceous we found significant differences between areas evidenced by Student's T-tests. The Spearman correlation test show positive correlation between Vachellia caven and soil conditions on grazed area and negatively correlated to total aboveground biomass of herbaceous extract which proves its better adaptation to grazing and intolerance to more levels of soil shading. Based on exploratory ordination analyses (PCoA) we can infer that there is a big difference between the two study areas that were shaped by remarkable changes in soil physical components, herbaceous vegetation and abundance of Prosopis affinis and Vachellia caven occurring just over five years of exclusion.